Corrosion of titanium alloys in pressurised water at 350 °C and 17.5 MPa. (June 2022) - Selva, Sabrina; Bignon, Quentin; Raynal, Amandine; Martin, Frantz; Auzoux, Quentin; Renou, Gilles; Latu-Romain, Laurence; Wouters, Yves
Abstract: The corrosion of titanium alloys in pressurised water at 350 °C and 17.5 MPa was studied in a loop made of stainless steel. The corrosion mechanism involved simultaneous TiO2 formation and dissolution, which led to surface precipitation of TiO2 anatase and FeTiO3 ilmenite crystallites. Based on image analyses made on cross-sections, a minimum corrosion rate, for all tested titanium alloys, was estimated at 4 µm year −1 at 350 °C. Comparison with a previous study indicated an increase of the corrosion rate by an approximate factor of 4 between 300 °C and 350 °C. Highlights: Three titanium alloys were exposed to water at 350 °C and 17.5 MPa. A continuous nanometric TiO2 layer was formed. Micrometric anatase and ilmenite crystallites precipitated. The corrosion rate was superior to 4 µm year −1 .